Drivers, Opportunities, and Challenges for Integrated Resource Co-management and Sustainable Development in Galapagos - Garcia Ferrari, Soledad; Bain, Amelia A.; Crane De Narváez, Stephanie (Frontiers in Sustainable Cities, 2021)
The Galapagos archipelago represents an insular system with finite natural resources, a growing population, and an economy heavily weighted on tourism that leaves it vulnerable to shocks, such as the Covid-19 crisis. This work proposes an alternative scenario developed through creating intersections between water-energy-food (WEF) nexus and adaptive co-management (ACM) approaches to resource management. This framework allows the identification of novel synergies that are applied to the analysis of Galapagos as case study. Within this approach, qualitative analysis is applied to data collected via a set of interviews with local stakeholders (including community, business, third sector and government actors) to evaluate (i) how a deeper understanding of community perceptions and needs can help to identify pathways towards more sustainable development in line with conservation goals, (ii) what governance frameworks should be implemented to promote community-based resource management and resilience, and (iii) what role education and capacitation can play in supporting alternative forms of economic activity. The research suggests that the implementation of an integrated WEF-ACM framework for resource management in Galapagos could promote resilience by opening a space for deliberation and conflict resolution between legitimate stakeholders, thus supporting more effective and balanced participative governance. The current Covid-19 crisis has led to the emergence of alternative forms of community collaboration that demonstrate the potential for a more economically diverse and more sustainable future. By placing different sources of knowledge on a level platform in such a framework, greater community ownership of resource management and conservation goals could be achieved. The incorporation of an ACM approach within the management of WEF resources would also allow Galapagueños to determine their own vision of a future sustainable socio-ecosystem, based on optimising system outcomes by co-identifying the trade-offs and synergies between the interrelated resource sectors, but requires a transformation in institutional culture.